The Impact of Compensation and Career Development on Turnover Intention With Job Satisfaction as Intervening Variable at PT Wijaya Machinery Perkasa - Sinaga, Marida; Ahmad Badawy Saluy; Novawiguna Kemalasari; Abdul Bari (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This research finds out and analyzes the impact of giving compensation and career development to turnover intention with job satisfaction level as an intervening variable at PT. Wijaya Machinery Perkasa. A quantitative descriptive method using a causal relationship approach was administered to conduct this research. The data analysis method used is Structural Equation Model (SEM) with SmartPLS (Partial Least Square) 3.0. The results of this study show; (1) Job satisfaction has significant effect and increases the trend on compensation, (2) Job satisfaction has positif impact on the career development, (3) Compensation trend is not significantly effective on turnover intention, (5) Job satisfaction as an intervening variable has low effect on compensation on turnover intention, (6) Career development has a negative effect on turnover intention, and (7) The employee turnover intention at PT. Wijaya Machinery Perkasa is not significantly effective on job satisfaction.